2010
DOI: 10.1088/1674-4527/10/2/003
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of optical spectral index and variability properties of S5 0716+714

Abstract: We analyze the spectral variability and spectral evolution in the optical energy region by using multiband (BVRI) optical observations of S5 0716+714 spanning 1994 to 2005. The spectrum hardens when the source becomes brighter, which is consistent with general BL Lac objects. The spectral evolution parameter implies that the spectral variability is small in optical bands over 10 years. A simple model representing the variability of a synchrotron component can explain the spectral changes. In addition, we emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
3
7
0
Order By: Relevance
“…It can be seen that the object shows strong BWB chromatisms on both intranight and internight timescales. This result is in agreement with several previous results (Wu et al 2005(Wu et al , 2007aHao et al 2010;Chandra et al 2011) and with the short-term behavior obtained by Ghisellini et al (1997) and Zhang et al (2008). The much larger correlation coefficient in the right panel indicates a stronger correlation between B ′ − R ′ and B ′ than between B ′ − V ′ and B ′ .…”
Section: Color-magnitude Correlationsupporting
confidence: 94%
See 1 more Smart Citation
“…It can be seen that the object shows strong BWB chromatisms on both intranight and internight timescales. This result is in agreement with several previous results (Wu et al 2005(Wu et al , 2007aHao et al 2010;Chandra et al 2011) and with the short-term behavior obtained by Ghisellini et al (1997) and Zhang et al (2008). The much larger correlation coefficient in the right panel indicates a stronger correlation between B ′ − R ′ and B ′ than between B ′ − V ′ and B ′ .…”
Section: Color-magnitude Correlationsupporting
confidence: 94%
“…In optical regime, several authors claimed no detection of inter-band delays (e.g. Hao et al 2010;Carini et al 2011). Some other claimed the opposite, as mentioned in §3.4.…”
Section: Discussion On Time Lagmentioning
confidence: 99%
“…The optical duty cycle of S5 0716+714 is nearly unity, indicating that the source is always in an active state in the visible (Wagner & Witzel 1995). Strong bluer-when-brighter correlations were found for both internight and intranight variations (Wu et al 2005(Wu et al , 2007(Wu et al , 2012Poon et al 2009;Hao et al 2010;Chandra et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, at the synchrotron frequencies, within the simplest scenario of single-zone emission models with homogeneous magnetic field distributions, clear patterns between the spectral index and the total intensity are predicted, i.e., a "spectral hysteresis", depending on the relative lengths of the radiative cooling timescale and the escape timescale of the accelerated particles from the emission zone (e.g., Kirk et al 1998). A significant fraction of long-term multiband flux monitoring studies have revealed bluer-when-brighter trends for BL Lac objects but frequently redder-whenbrighter trends for FSRQs (Gu et al 2006;Osterman Meyer et al 2009;Rani et al 2010;Hao et al 2010;Ikejiri et al 2011;Bonning et al 2012;Sandrinelli et al 2014;Meng et al 2018;Li et al 2018;Gupta et al 2019) while 'achromatic' flux variability (no colour evolution, Gaur et al 2019;Bonning et al 2012;Stalin et al 2006), and erratic patterns (Wierzcholska et al 2015) have also been reported. It has been argued that particles accelerated to higher energies are injected at the emission zone before being cooled radiatively in BL Lac sources leading to their overall SEDs being bluer-when-brighter; however, the 'redder' and more variable jet-component can overwhelm the 'bluer' contribution from the accretion disc, leading to redder-when-brighter trends for FSRQ type sources (Gu et al 2006).…”
Section: Introductionmentioning
confidence: 99%